Analysis of fungal microbiota diversity and potential pathogenic fungi in oral secretions and gut feces of captive giant pandas - Ma, Xiaoping; Zeng, Xiangwen; Huang, Zhi; Li, Gen; Liu, Ruiguo; Luo, Rongyan; Li, Xinni; Ling, Shanshan; Wang, Chengdong; Gu, Yu (Frontiers in Microbiology, 2025)
BackgroundMaintaining good oral and gut health is essential for the wellbeing of animals, and fungi are key components of the oral and gut microbiota. This study aims to explore the diversity and seasonal dynamics of oral and gut fungal communities in captive giant pandas, with a focus on their potential functional roles in health and digestion.MethodsIn the study, we collected saliva and fecal samples from 60 captive giant pandas were collected in different seasons, oral and gut fungi were analyzed using internal transcribed spacer (ITS) amplicon sequencing. We used α and β diversity analyses to examine the differences in species diversity and composition among the different seasons. Furthermore, we validated the ITS amplicon sequencing results through fungal isolation and identification.ResultsAnalyses of α and β diversity revealed both the differences and similarities between the fungal communities in the oral and gut microbiomes of giant pandas. Ascomycota and Basidiomycota were predominant in both oral and gut groups, while the dominant genera in the four seasons were Cutaneotrichosporon, and unidentified_Chaetothyriales_sp. Additionally, Cladosporium and Candida were predominant in the oral and gut fungus, respectively, across all four seasons. Notably, fungal abundance and diversity in the oral microbiome were significantly higher than in the gut microbiome, a pattern observed throughout most seasons. Several potentially pathogenic fungi, such as Fusarium, Candida and Aspergillus, were detected in healthy giant pandas, with most showing increased abundance during winter. It is worth mentioning that we found a distinct bias in the functional communities of oral and gut fungi. The abundance of saprophytic fungi in the gut is relatively high, which may be related to their role in cellulose digestion.ConclusionThe abundance and diversity of fungal communities in the oral cavity and gut of giant pandas exhibit significant seasonal variations. While the oral cavity hosts a higher abundance and diversity of fungi, the species composition of fungal community composition is similar to that of the intestines. The majority of gut fungi are likely derived from the oral cavity or diet, the significant seasonal variation in gut fungal community structure further suggests that long-term resident fungi may not be present in the gut.